2010
DOI: 10.1152/ajprenal.00639.2009
|View full text |Cite
|
Sign up to set email alerts
|

p66SHC-mediated mitochondrial dysfunction in renal proximal tubule cells during oxidative injury

Abstract: Mitochondrial dysfunction is involved in pathopysiology of ischemia-reperfusion-induced acute kidney injury (AKI). The p66shc adaptor protein is a newly recognized mediator of mitochondrial dysfunction, which might play a role in AKI-induced renal tubular injury. Oxidative stress-mediated Serine36 phosphorylation of p66shc facilitates its transportation to the mitochondria where it oxidizes cytochrome c and generates excessive amount of reactive oxygen species (ROS). The consequence is mitochondrial depolariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 49 publications
1
61
0
Order By: Relevance
“…They are also protected from the development of diabetic glomerulopathy, presumably due to a blockade of hyperglycemia-induced ROS production (23). Furthermore, it has been reported that the p66Shc mediates mitochondrial dysfunction in renal proximal tubule cells in the ischemia-reperfusion injury model (1), and ANG II induced apoptosis in myocardial cells (10). These literature reports certainly establish the role of p66Shc in states of oxidant stress.…”
mentioning
confidence: 85%
“…They are also protected from the development of diabetic glomerulopathy, presumably due to a blockade of hyperglycemia-induced ROS production (23). Furthermore, it has been reported that the p66Shc mediates mitochondrial dysfunction in renal proximal tubule cells in the ischemia-reperfusion injury model (1), and ANG II induced apoptosis in myocardial cells (10). These literature reports certainly establish the role of p66Shc in states of oxidant stress.…”
mentioning
confidence: 85%
“…p66sch is known as a pro-oxidant enzyme that links oxidative stress to renal injury (2,8,23,24). Interestingly, lately some studies -including ours (17)-revealed that under certain circumstances p66shc can serve as an antioxidant (25).…”
Section: Discussionmentioning
confidence: 86%
“…Extent of cell injury was determined by LDH release using the fluorescent "Cytotox-One Homogeneous Membrane Integrity" kit (Promega, Madison, WI) as described earlier (13). Briefly, cells grown in 96-well-plates were transfected and treated as described in the appropriate section and 24 h later LDH content of the supernatants were determined and compared to total 4075 This article is freely accessible online.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, cells grown in T25 flasks and treated with 20 μM RES or vehicle overnight were collected, counted and loaded with 100 μM DCFDA for 30 min. After washing away the excess dye equal number (0.5×10 6 ) of cells were distributed in a 96-well plate; 200 μM NIC was added and ROS production was immediately determined as described elsewhere (15). ROS production was calculated as the increase in fluorescence/30 min/0.5×10 6 cells and expressed as a percentage of that of corresponding untreated cells.…”
Section: Methodsmentioning
confidence: 99%